Effects of High Temperature Oxidation on the Structure and Properties of NiTi Alloy - Wang, Jing; Xiao Tian Wang, Bo (Asian Journal of Chemistry, 2012)
In order to explore the ideal thermal oxidation process of NiTi alloy, mechanical polishing NiTi alloy were treated at different temperatures (400, 500 and 600 ºC) and the water affinity, superelasticity and corrosion resistant were investigated. The results indicated that the hydrophilicity and hydrophobicity, super-elasticity and corrosion resistant of the sample, which treated at 500 ºC for 0.5 h and natural cooled in the air was more ideal compared with other samples.